The Development of Multidisciplinary Care System for Patients Receiving Warfarin by Using Self-management Combined with Case Management in Nawa Hospital Nakhon Phanom Province: การพัฒนาระบบการดูแลผู้ป่วยที่ได้รับยาวาร์ฟารินแบบสหวิชาชีพ โดยใช้แนวคิด การจัดการตนเองร่วมกับการจัดการรายกรณี โรงพยาบาลนาหว้า จังหวัดนครพนม - suntrarak, orachon (Journal of Nursing and Health Sciences Nakhon Phanom University, 2023)
This action research aimed to develop and evaluate multidisciplinary care system for patients receiving warfarin by using self-management combined with case management in Nawa hospital Nakhon Phanom province. The period was from April – October 2023. Research participants include 1) a group of 10 system developers and 2) a group of 40 patients receiving warfarin at the warfarin clinic Nawa Hospital. Research participants were selected using purposive sampling. The research instrument were self-care knowledge test, behavior questionnaire form, Follow-up form for adverse events from warfarin use, and patient satisfaction assessment form. Data were analyzed by finding frequencies, percentages, means, and standard deviations. Comparatived analysis, average scores of self-care knowledge, self-care practice, and satisfaction of patients receiving warfarin, before and after system development using t-test (paired samples). Analyzed qualitative data by content analysis. The research results found that Process results. A system for caring for patients receiving warfarin was born. Healthcare team had clear guidelines for caring for patients receiving warfarin (CPG). Care for patients receiving warfarin was classified according to International Normal Ratio (INR). Organized a warfarin clinic with one stop service, multidisciplinary team readied to serve patients. And the patient had a self-management manual for patients receiving warfarin. Resultant results. 2.1 patient were received continuous care according to developed indicators. 2.2 Patients had an average score of self-care knowledge, Self-care practices and satisfaction, after system development was higher than before system development, statistically significant (p< 0.05).